PHRASAL VERBS IN MODERN ENGLISH LANGUAGE - Latypova, E. N. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
This article describes the relevance of using phrasal verbs in English. The general concept of phrasal verbs is also disclosed. A brief description of the history of the development of phrasal verbs in different periods of time is given. It is concluded that the use of phrasal verbs significantly expands the vocabulary.
Keywords: phrasal verbs; dictionary; lexicology; linguistics; English; science